The effectiveness of role-playing assisted by finger puppet media in improving elementary school students’ speaking skills: a literature review - Dita Aulia Nafisah; Lina Siti Nurwahidah; Yennie Indriati Widyaningsih (STKIP Melawi, 2026)
Speaking skills are a fundamental component of communication. However, elementary school students often encounter affective barriers that reduce their confidence in expressing ideas orally. This study aims to synthesize the effectiveness of integrating a role-playing model assisted by finger puppet media in improving students' speaking skills. The study employed a qualitative systematic literature review using the PRISMA protocol, with articles obtained from Sinta-indexed journals and other relevant scholarly databases published between 2016 and 2026. The synthesis of six selected studies shows that the integration of role playing and finger puppet media supports the development of speaking skills through structured role-playing simulations. Finger puppets function as scaffolding that helps reduce emotional barriers, enabling students to speak more more confidently and effectively. This study is limited by the small number of articles analyzed and the grade-level scope of the reviewed studies. Therefore, the findings may serve as a theoretical reference for teachers in designing innovative communicative learning in elementary schools.